2016
DOI: 10.3899/jrheum.151132
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Remission and Low Disease Activity Definitions in Patients with Rheumatoid Arthritis in Clinical Practice: Results from the NOR-DMARD Study

Abstract: In daily clinical practice, the DAS28 and RAPID3 definitions identified remission about twice as often as the ACR/EULAR Boolean, SDAI, and CDAI. Predictors of remission were similar across remission definitions. These findings provide additional evidence to follow treatment recommendations and treat RA early with a DMARD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…The seronegative patients had the highest levels of inflammation at baseline,(7) but these patients had, nevertheless, two-year remission rates comparable to the seropositive patients suggesting good response to modern treatment. (200) Very early arthritis (defined as symptom duration less than three or six months) are highlighted as the most important factor for reaching remission, (73,74,201) and our study supports DMARD initiation within 3 months after symptom onset. As symptom onset was defined as the first swollen joint according to patient memory, there is a chance of recall bias.…”
Section: Prediction Of Sustained Remission In Early Rasupporting
confidence: 70%
“…The seronegative patients had the highest levels of inflammation at baseline,(7) but these patients had, nevertheless, two-year remission rates comparable to the seropositive patients suggesting good response to modern treatment. (200) Very early arthritis (defined as symptom duration less than three or six months) are highlighted as the most important factor for reaching remission, (73,74,201) and our study supports DMARD initiation within 3 months after symptom onset. As symptom onset was defined as the first swollen joint according to patient memory, there is a chance of recall bias.…”
Section: Prediction Of Sustained Remission In Early Rasupporting
confidence: 70%
“…Several prior studies showed that women are less likely to achieve remission when using the DAS28-ESR (1,2,9,14), but there are less consistent findings in studies examining the performance of CDAI and RAPID3 (5,9,14). Our study confirmed that women are less likely to reach remission when defined by the DAS28-ESR.…”
Section: Discussionsupporting
confidence: 54%
“…In a study from the Corrona RA registry, a large prospective cohort study, women were less likely to achieve CDAI early sustained remission , but there was no difference in established remission or in early point remission. Another recent study showed that women were less likely to achieve remission when it was defined by DAS28‐ESR, CDAI, and the Simple Disease Activity Index but found no difference in remission rates for Boolean criteria or RAPID3 . Overall, these studies suggest a more refractory phenotype among women, but the results lack consistency and vary based on the composite outcomes used and population studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible reason for this may be that biological treatment in Austria is initiated in patients with milder disease than in other countries [14]. Better outcomes in milder than higher diseased patients are underlined by a recent study conducted in a five-centre Norwegian register [15], as well as in the German register RABBIT, which recorded a 30 % DAS28 remission rate when bDMARD therapy was started in moderate DA [16]. …”
Section: Discussionmentioning
confidence: 99%